MANAJEMEN PENDIDIKAN SEKOLAH GRATIS - Humairah Humairah (Jurnal Manajemen Pendidikan, 2015)
The objective of this research is to gain a through understanding about management of quality of Tuition- free school. It is a qualitative research with a case study method conducted in Indonesia Juara Foundation using observation on school management implementation in SD Juara South Jakarta, since February-June 2015. The data were collected from participants observation using interview, observation, documents study and recordings. Data analysis and interpretation show that (1) Professional HR management is started from recruiting process, evaluating HR need, performance appraisal, coaching and counselling. (2) effective management of donation based on transparent and accountable implementation report of the fund-usage and implementation of qualified program in the school, report accuracy, trust to the benefactors and fund allocating for HR (3) The quality and the excellence of the school are based on the availability of competent HR and professional management as well as well-managed system and fund. The findings lead to the recommendation that (1) there is a need for a clear framework for teacher to do his duties, scheduled monitoring/evaluation (2) fund-absorption priority should be matched to program budget plan, alternative fund resources from government such as BOS. (3) there is a need for standardized management of quality as a special characteristic of Sekolah Juara. It is also recommended for decision makers at free schools as motivation and reference to improve their quality and service.